Pendampingan Pengembangan UMKM dengan Transformasi ke Bisnis Syariah : Pengurusan NIB & Pembiayaan Pelaku UMKM Kota Padang - Fitri, Radia; Afriyanti, Afriyanti; Ulyadi, Ulyadi (Jurnal Pengabdian UNDIKMA, 2024)
This service aims to increase the understanding of UMKM players regarding the development of UMKM with their transformation into sharia business. Understanding Sharia business was focused on anti-usury Sharia financing. Apart from understanding financing, they were also assisted in issuing NIB and financing to Islamic banking institutions. The method of this service was Participatory Action Research (PAR), where the team accompanies Padang City UMKM (Micro, Small and Medium Enterprises) actors. Evaluation was carried out by sharing experiences from UMKM actors, feedback, and follow-up. Data analysis used in this service used descriptive analysis. The success of this activity was measured by the understanding provided to UMKM actors regarding the Sharia business. The results of this service showed that UMKM actors  understood Sharia business principles; UMKM actors proved this: 1) Wanting to switch to a Sharia institution in accordance with applicable regulations, 2) Registering as Nagari Syariah bank customers, 3) Registering their business to get NIB because including the requirements for financing files and processing halal certificates, 4) Registering the business to obtain Sharia capital, 5) Filling in the halal certificate issuance form to obtain a halal certificate.